Indigenous knowledge in the built environment : a guide for tertiary educators. - Jones, David S.; Choy, Darryl Low; Tucker, Richard; Heyes, Scott; Revell, Grant; Bird, Susan (Australia. Dept of Education and Training (DET), 2018)
The Guide is purposely intended as a teaching and learning resource kit for built environment (architecture, landscape architecture, planning) academics, students and professional practitioners. Not exhaustive, it is a substantive starting point for aiding the formulation of units/courses/programs of study, as well as professional practice activities, that address, involve, and implicate Indigenous issues, topics, places, representatives and communities. The Guide offers immediate assistance in informing built environment academics, students and professional practitioners about initial protocols and resources that they need to heed, be mindful of, and have available to them, that may be directly pertinent to their research activities; to their design ideation and studio work; to their drafting of plans and strategies; and, to their formulation of strategies for contact, engagement and consultation. It includes: architecture, landscape architecture and planning precedents around Australia, and key architecture, landscape architecture and planning / Country literature and resources that could inform their design and or planning activities. In tabling this Guide, the authors offer this Guide and its contents to Aboriginal and Torres Strait Islander education centres and schools to develop and acknowledge that further consultation is required with the respective university Aboriginal and Torres Strait Islander education centres and schools, or Elders, to develop these protocols and resources into workable ways of Indigenising planning and design higher education curriculum and professional practices. Similarly it is available to the built environment professions. [The Guide]